2022
DOI: 10.9734/ajpr/2022/v10i3199
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Plasma Homocysteine Level in Children with Autism

Abstract: Background: Autism is a neurodevelopmental disorder that appears in early life. B6 and B12, and folate support homocysteine (Hcy) metabolism. Hence, any defect to them leads to Hcy accumulation in the body. Hcy, vitamins B12, B6 and folate are important in psychiatric disorders such dementia, schizophrenia, and autism. This study intended to compare the plasma Hcy levels in normal and autistic cases to find out whether there is difference between the levels of Hcy in plasma of autistic and normal children.�… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Vitamin B12 and folate, the two main key regulators of the folate–methionine cycle, are required for homocysteine metabolism. Hence, any defect in them leads to homocysteine accumulation in the body, thus leading to neurotoxicity, oxidative stress, and mitochondrial dysfunction [ 49 , 50 ]. In fact, several studies reported that children with ASD had lower levels of vitamin B12 and folate and higher levels of homocysteine compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 and folate, the two main key regulators of the folate–methionine cycle, are required for homocysteine metabolism. Hence, any defect in them leads to homocysteine accumulation in the body, thus leading to neurotoxicity, oxidative stress, and mitochondrial dysfunction [ 49 , 50 ]. In fact, several studies reported that children with ASD had lower levels of vitamin B12 and folate and higher levels of homocysteine compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Centro Universitário das Faculdades Metropolitanas Unidas (FMU) 2. Nutricionista pela Pontifícia Universidade Católica de Campinas, especialista em Nutrição, Saúde e Qualidade de Vida pela Unicamp, mestre e doutora em Ciências pela Universidade Federal de São Paulo -UNIFESP.…”
unclassified